Degraded DNA typing highly improved by a CODIS-CORE + ESS MEGAPLEX based on superprimers. Issue 1 (December 2019) - Mautner, Martin E.; Caputo, Mariela; Ginart, Santiago; Bengochea, Tatiana S.; Corach, Daniel
Abstract: On degraded DNA samples a multiplex PCR mixture containing polynucleotide primers can provide superior genotyping of Short Tandem Repeats (STRs) to the current commercial kits based on standard oligonucleotides.